ANALISIS FAKTOR- FAKTOR RISIKO KESEHATAN PADA PETANI TOMAT TERHADAP PAPARAN PESTISIDA KLORPIRIFOS DI WILAYAH PUSKESMAS BUKIT KABUPATEN BENER MERIAH - Humaira; Elyarianti; Alamsyah, Sanjaya (Akper Kesdam I/Bukit Barisan Padang, 2025)
ABSTRACT Pesticides are one of the important substances in agriculture that can help farmers and have an important role in overcoming the problem of pest organisms on agricultural land. Pesticides are one of the important substances in agriculture that can help farmers and have an important role in overcoming the problem of pest organisms on agricultural land. Farmers' knowledge also influences the causes of poisoning caused by the use of pesticides. The level of knowledge will influence the incidence of pesticide poisoning in farmers, especially if farmers do not use Personal Protective Equipment (PPE). The aim of this research is to analyze the health risks of tomato farmers regarding exposure to the pesticide chlorpyrifos in the Bukit Health Center area, Bener Meriah Regency in 2024. This research design uses analytical descriptive with a cross sectional study design. The samples taken were 54 respondents. The sampling technique uses random sampling technique, namely random sampling. This research was carried out in the Bukit Health Center area of Bener Meriah Regency from 12 July to 04 August 2024. The results of statistical analysis using the Chi Squer test obtained a P value = 0.001 < 0.05, this shows that there is a relationship between the knowledge of tomato farmers and exposure. Chlorpyrifos pesticide, P value = 0.003 < 0.05, this shows that there is a relationship between the attitudes of tomato farmers towards exposure to the pesticide chlorpyrifos, and the P value = 0.002 < 0.05, this shows that there is a relationship between the use of personal protective equipment for tomato farmers and exposure. Chlorpyrifos pesticide in the Bukit Bener Meriah District Health Center area in 2024. It is hoped that this research can bring changes in society for the better, especially for the people in the Bukit Bener Meriah District Health Center working area and provide new knowledge about Health Risk Factors for Farmers Tomatoes Against Exposure to the Pesticide Chlorpyrifos. Keywords : Knowledge, Attitude, Use of Personal Protective Equipment, Exposure Chlorpyrifos pesticide